A review of the genera Elydnodes Hampson, 1913 and Antitrisuloides Holloway, 1985 with description of two new species (Lepidoptera, Noctuidae). Revision of Pantheinae, contribution III - Behounek, Gottfried; Kononenko, Vladimir (Zootaxa, 2011)
Two genera in the noctuid subfamily Pantheinae are revised: Elydnodes Hampson, 1913 and Antitrisuloides Holloway, 1985. Two new species (Elydnodes griseata sp. n. and Antitrisuloides siamensis sp. n.) are described from Thailand, Laos and Malaysia.